Combat Training for Horse and Rider in the Early Middle Ages - Gassmann Jürg (Bern Open Publishing, 2018)
The cavalry horse, tactics and training in Western Europe - the Euro-pean provinces of the Roman Empire of the West and the Frankish Empire - du-ring the Early Middle Ages (c. 500-1000) are still subject to many myths in both popular media and academic literature. Source material is admittedly thin, yet it is specific enough to allow us to correct many of these misconceptions and outright errors.